2022
DOI: 10.1108/ohi-08-2021-0174
|View full text |Cite
|
Sign up to set email alerts
|

Vernacular architecture of Turkish eastern Black Sea region: a case study in Senoz (Büyükdere) Valley

Abstract: PurposeThis paper aims to elaborate on the characteristics of vernacular architecture, particularly the architecture of the Turkish eastern Black Sea region, through a case study in the area; and to attract the attention of architects and researchers on the unique characters of the region. Another aim of the paper is to examine the contribution of vernacular architecture to sustainability through its design methods and principles, which have been developed throughout centuries.Design/methodology/approachThis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The local wisdom was also explained as a distinctive form of community expression and can adapt to the times without losing its local character [18,30,32,36]. This means the positive values inherent in the culture need to be preserved as essential lessons for future generations [19,20,38] (see Table 1).…”
Section: Culture and Local Wisdommentioning
confidence: 99%
See 1 more Smart Citation
“…The local wisdom was also explained as a distinctive form of community expression and can adapt to the times without losing its local character [18,30,32,36]. This means the positive values inherent in the culture need to be preserved as essential lessons for future generations [19,20,38] (see Table 1).…”
Section: Culture and Local Wisdommentioning
confidence: 99%
“…Moreover, its functionality responds to changes and the needs of different times while maintaining the local essence [18]. Ceylan [19] showed that the unique character of the architecture needs to be protected and maintained to allow future generations to also benefit from design features. The first step to the protection is knowing and appreciating the vernacular heritage and demonstrating a commitment to future generations [20].…”
Section: Introductionmentioning
confidence: 99%
“…This has also been studied and explored by many scholars. Globalization, which seeks to bring world societies closer together and form a single entity based on commerce, politics, and communication, diminishes the significance of cultural variations across societies and, consequently, local cultural identities (Ceylan, 2022). In addition, residential houses account for a large share of the building stock in developing countries and can have a lasting impact on the local and global economy and environment.…”
Section: Introductionmentioning
confidence: 99%